TBMs alternative to D & B in tunnel excavation - Giraldo Paredez, Emiliano Mauro (2010)
The Drilling and Blasting (D & B) in tunneling, has been replaced by a variety of types and sizes of tunneling machines (TBMs) for technological progress, productivity demands and environmental control. This study is intended as a framework for selecting the most suitable system of excavation under a minimum length to justify its application. Both the TBM MK 12 and the D & B were studied in the headrace tunnel No. 4 Hydroelectric Project Yuncan. We show that for digging long tunnels, TBM have greater advantages than the D & B, plus the minimum disturbance to the remaining rock, speed of excavation, increased safety for personnel and equipment, lack of gas blasting, minor excavation area, among others.